The influence of sensitization and corrosion on creep of 5083-H116. (October 2018) - Mills, Robert J.; Lattimer, Brian Y.; Case, Scott W.; Mouritz, Adrian P.
Highlights: As-received and sensitized 5083-H116 behave similarly in high temperature creep. All 5083-H116 damaged states failed alike at the extreme case of 400 °C and 18 MPa. The Kachanov-Rabotnov model was applied to sensitized and corroded 5083-H116. Adjusted for remaining section, corroded and uncorroded samples had akin lifetimes. Abstract: Elevated temperature exposure of 5XXX alloys causes sensitization, which leads to changes in room temperature mechanical properties and may lead to intergranular corrosion (IGC) susceptibility. The influence of sensitization and corrosion damage on the creep response of 5083-H116 at various temperatures (representative of fire damage) from 200 °C to 400 °C has been examined in this experimental study. Sensitization had a negligible effect on creep properties, while corrosion damage led to a reduction in creep rupture time and steady state creep rates. After accounting for sensitization and corrosion damage, creep rupture can be predicted based upon secondary creep/steady state creep rates.